(untitled) (Research, Society and Development, 2023)
The objective of this work was to carry out a diagnosis with beekeepers in the Jequitinhonha Valley region and others involved in the beekeeping activity, in order to verify the potential of mastic honey to obtain the Geographical Indication. A questionnaire was applied with beekeepers and interviews with key representatives. The results showed that there is a great potential to achieve the GI for Jequitinhonha honey. It was noticed that in terms of technical viability (distinction of regional products and their connections with local natural and human factors, as well as their controllability), commercial viability (market trends and willingness to pay for special products) and organizational viability (the dynamism and structure of the value chain), Jequitinhonha honey must be worked on by all actors in the production chain in favor of GI. A “gold standard” sample was sent for analysis of botanical origin at the FUNED laboratory, and respectively 99.6% and 98.8% of mastic pollen grains were obtained. Honey was able to obtain scores in the main viability dimensions for Geographical Indications. This approach will require extensive collaboration within the honey value chain itself, national and regional authorities, and specialists in honey production, marketing, and studies. Therefore, the analysis attests to the potentiality of Jequitinhonha honey for Geographical Indication by the INPI, since the challenges to be overcome must be worked together.